Helping Ease during Marriage: Tombor Magh as Social Ties among Family Members of Fakfak Family, West Papua, Indonesia - Abza, M. Thohar Al; Purwati, Heni; Yusuf, Muhamad; Zulihi, Zulihi; Iribaram, Suparto (LP2M - Universitas Islam Negeri Walisongo Semarang, 2024)
A tradition that is still carried out by the Patipi Pulau community of Fakfak Regency is the collection of dowry called the Tombor Magh tradition, which is determined by the female party to the male party through an agreement. The aim of the research is to determine the implementation of the Tombor Magh tradition and the impact of the Tombor Magh tradition carried out by the Patipi Island indigenous community in Fakfak Regency. This is qualitative research, using a social phenomenology paradigm. Research results the Tombor Magh tradition (collection of dowry) is carried out when marriages occur between members of the Fakfak traditional community. The Tombor Magh tradition is carried out at the groom's house. In tradition, there are reciprocal gifts made by the groom's family to cover the groom's lack of dowry. Giving to women is a gift. When Tombor Magh is not fulfilled, the consequences are borne by the man. The delivery objects in Tombor Magh are jumhur, ndrup, pdour, yana, mongmongka, lela, nteing, and antique plates. The function of Tombor Magh is to maintain community culture as a means of unifying, strengthening, and binding the family, maintaining the integrity of family relationships, maintaining traditions passed down from generation to generation, and maintaining the honor and dignity of the male family in fulfilling the dowry. If you don't implement Tombor Magh, there are consequences that must be obeyed, which are habits that arise from mutual agreements that have become the customary law of the community by discarding the surname/family/clan from men to be passed on to their children, which is used is the surname/family/clan.